Debt and Sad Affects in the Society of Control - Młoźniak, Iwona (Conatus - Journal of Philosophy, 2018)
The article presents an analysis of the notion of debt in the context of Deleuzean philosophy of affect. The interpretation presented on the following pages is “indebted” to Lazzarato’s conception of the notion of debt as a figure of subjectivity typical for capitalism. Debt is understood as an assemblage of sad passions and considered in relation to social transformations, that have led to contemporary societies of control.  The article shows the connection between the concept of debt and the process of individualization characteristic for contemporary society. Firstly, the concepts of control, debt and affect in the philosophy of Deleuze are put into consideration. Secondly, their relation to the forces and assemblages typical for contemporary societies is discussed. In order to grasp the social significance of the philosophical analysis, the article involves a sociological excursion that demonstrates sociological interpretation of the processes that were described in terms of philosophical analysis in the main body of the text.